2001
DOI: 10.1177/000331970105201010
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis Caused by Congenial Interruption of the Inferior Vena Cava

Abstract: Congenital interruption of the inferior vena cava is an uncommon vascular anomaly. In this setting, the appearance of deep vein thrombosis is very rare because associated azygous or portal continuation develops as a collateral system for venous return. The authors present a case of infrahepatic interruption of the inferior vena cava in a 21-year-old man who presented with symptoms of deep vein thrombosis. Clinical features and prognosis of this entity are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 17 publications
0
39
0
1
Order By: Relevance
“…7 Pyrexia can be present, as described by Tsuji et al, who reported a series of 10 patients where 40% were pyrexic at presentation. 57 …”
Section: Acute Ivc Thrombosismentioning
confidence: 99%
See 2 more Smart Citations
“…7 Pyrexia can be present, as described by Tsuji et al, who reported a series of 10 patients where 40% were pyrexic at presentation. 57 …”
Section: Acute Ivc Thrombosismentioning
confidence: 99%
“…Biochemical renal dysfunction may suggest ureteric obstruction secondary to retroperitoneal fibrosis or renal vein thrombosis. 57 Though largely directed from Level IV evidence, it would appear prudent to perform a thrombophilia screen, especially in young patients without other risk factors. This should include: protein C, antithrombin, free protein S, activated protein-C resistance, IgG anticardiolipins, lupus anticoagulant and homocysteine levels as well as a PT (20210) FII gene mutation screen.…”
Section: Haematologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Although less commonly, complete or partial agenesis of the IVC may also present concomitantly with other organ abnormalities, such as congenital heart defects (dextrocardia, septal defects, pulmonary artery stenosis, single atrium, and transposition of great vessels), polysplenia, asplenia, inversion of bowel viscera, and kidney hypoplasia. 15,16 The impact of IVC agenesis in the long-term prognosis of DVT is still unclear. 8 Patients are generally advised to maintain anticoagulation for at least three months following DVT to avoid early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recent advances in the utilisation of ultrasound, CT and MRI imaging as well as endovascular procedures have resulted in an increase in detection rates of IVC anomalies as well as the incidental discovery of such abnormalities during unrelated investigations and therapeutic endovascular or surgical procedures. 5 Contrast venography remains the standard for diagnosis of IVC thrombosis with a low false-positive rate and the advantage of access for immediate treatment if required.…”
Section: Investigationsmentioning
confidence: 99%